Secondary prevention medication persistence and prognosis of acute ischaemic stroke or transient ischaemic attack. Issue 3 (1st February 2021) - Zhang, Lei; Shi, Junfeng; Pan, Yuesong; Li, Zixiao; Yan, Hongyi; Liu, Chelsea; Lv, Wei; Meng, Xia; Wang, Yongjun
Abstract : Introduction: The risk of disability and mortality is high among recurrent stroke, which highlights the importance of secondary prevention measures. We aim to evaluate medication persistence for secondary prevention and the prognosis of acute ischaemic stroke or transient ischaemic attack (TIA) in China. Methods: Patients with acute ischaemic stroke or TIA from the China National Stroke Registry II were divided into 3 groups based on the percentage of persistence in secondary prevention medication classes from discharge to 3 months after onset (level I: persistence=0%, level II: 0%<persistence<100%, level III: persistence=100%). The primary outcome was recurrent stroke. The secondary outcomes included composite events (stroke, myocardial infarction or death from cardiovascular cause), all-cause death and disability (modified Rankin Scale score=3–5) from 3 months to 1 year after onset. Recurrent stroke, composite events and all-cause death were performed using Cox regression model, and disability was identified through logistic regression model using the generalised estimating equation method. Results: 18 344 patients with acute ischaemic stroke or TIA were included, 315 (1.7%) of whom experienced recurrent strokes. Compared with level I, the adjusted HR of recurrent stroke for level II was 0.41 (95% CI 0.31 to 0.54) and level III 0.37 (0.28 to 0.48); composite events for level II 0.41 (0.32 to 0.53) and level III 0.38 (0.30 to 0.49); all-cause death for level II 0.28 (0.23 to 0.35) and level III 0.20 (0.16–0.24). Compared with level I, the adjusted OR of disability for level II was 0.89 (0.77 to 1.03) and level III 0.82 (0.72 to 0.93). Conclusions: Persistence in secondary prevention medications, especially in all classes of medications prescribed by the physician, was associated with lower hazard of recurrent stroke, composite events, all-cause death and lower odds of disability in patients with acute ischaemic stroke or TIA.